Current Status, Diagnosis, and Treatment Recommendation for Tic Disorders in China - Liu, Zhi-Sheng; Cui, Yong-Hua; Sun, Dan; Lu, Qing; Jiang, Yu-Wu; Jiang, Li; Wang, Jia-Qin; Luo, Rong; Fang, Fang; Zhou, Shui-Zhen; Wang, Yi; Cai, Fang-Cheng; et al. (Frontiers in Psychiatry, 2020)
Tic disorders (TD) are a group of neuropsychiatric disorders with childhood-onset characterized by tics, i.e. repetitive, sudden, and involuntary movements or vocalizations; and Tourette syndrome (TS) is the most severe form of TD. Their clinical manifestations are diverse; and are often associated with various psychopathological and/or behavioral comorbidities, including attention deficit hyperactivity disorder (ADHD), obsessive-compulsive disorder (OCD), anxiety, depression, and sleep disorders. Individual severity and response to treatment are highly variable, and there are some refractory cases, which are less responsive to conventional TD treatment. TD/TS is also common in the Chinese pediatric population. To help improve the understanding of TD for pediatricians and other health professionals, and to improve its diagnosis and treatment in China, the Chinese Child Neurology Society (CCNS) has developed an Expert Consensus on Diagnosis and Treatment of TD in China, which is based on our clinical experience and the availability therapeutic avenues. It is focused on clinical diagnosis and evaluation of TD and its comorbidities, psychological and educational intervention, nonpharmacological therapy, pharmacological treatment, including traditional Chinese medicine and acupuncture, as well as prognosis in children with TD in China. A summary of the current status of TD and up-to-date diagnosis and treatment recommendations for TD in China is presented here.